ANALISIS GADAI EMAS IB BAROKAH BERDASARKAN FATWA DSN MUI PADA BANK JATIM SYARIAH SAMPANG - Mujibno Mujibno; Riskiana Elina; Faizah Fauziyah (Bayan lin-Naas : Jurnal Dakwah Islam, 2021)
One of the most popular and most helpful sharia banking products for customers is financing products such as mortgage products. Pawn products are a superior product in Bank Jatim Syariah Sampang where it has 70% of all financing customers so that it has its own counter which is adjacent to the teller section. Of the large number of mortgage customers, it is certain that the mace team from Bank Jatim Syariah Sampang will find and face several risks. This risk must be minimized by using risk management. In this study, the author will explain how Bank Jatim Syariah implements 5C in risk management of Gold iB Barokah products by using a qualitative research type through a descriptive approach. The results of this study, the authors found the ability and form of success carried out by Bank Jatim Syariah Sampang in empowering its customers and how to analyze new customers to avoid other higher risks through 5C analysis (Character, Capacity, Capital, Collateral and Condition)